DETERMINATION OF THRESHOLD CURRENT DENSITIES FOR DIFFERENT REACTION OF FISHES USING A PANTOSTST - BISWAS, K P (Fishery Technology, 2025)
The threshold current densities required for first reaction,galvanotaxis and galvanonarcosis of fish depended upon species,length of the body. conductivity of water, nature of current andfrequency of impulses. The threshold values and their ratiosdecreased with increase in length of fish. With rise in conductivityof water in . the ratio of 1:4:13, these values increased inthe ratio 1 : 2 :-5; -Impulse D. C was superior to continuous D. Cand the threshold values of current densities for different reactions offish decreased with rise in impulse frequency reaching minimum atan impulse frequency of 48/sec. Among Safmo irideus, ldus melanotusand Cyprinus carpio, the first one was affected earlier and requiredminimum current densities to exhibit the reactions, while the lastone showed similar reactions only at higher current densities.